2008
DOI: 10.1177/1471301207085365
|View full text |Cite
|
Sign up to set email alerts
|

Collective strength

Abstract: Current theories of social power suggest that development of a shared social identity can create the possibility of bringing about political and attitudinal change as well as benefiting individual psychological well-being. This exploratory, qualitative, internet-based study extending over two years explored the impact of developing a shared social identity among a group of people with early-stage dementia. We investigated the experience of belonging to the self-help network Dementia Advocacy and Support Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 32 publications
2
90
0
Order By: Relevance
“…Söderhamn et al 2014Clare et al 2008Leung et al 2015;Toms et al 2015;Keyes et al 2016 Planning ahead for future impact of the condition with the aim of increased sense of control. Robinson et al 2015;Grand et al 2011;SCIE, 2015; Alzheimer's Association; Hellström & Torres, 2016 Adapting activity to capability Adapting capability to activity (and goals of activities), in order to feel that activities are manageable and successful.…”
Section: Methodsmentioning
confidence: 99%
“…Söderhamn et al 2014Clare et al 2008Leung et al 2015;Toms et al 2015;Keyes et al 2016 Planning ahead for future impact of the condition with the aim of increased sense of control. Robinson et al 2015;Grand et al 2011;SCIE, 2015; Alzheimer's Association; Hellström & Torres, 2016 Adapting activity to capability Adapting capability to activity (and goals of activities), in order to feel that activities are manageable and successful.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, people described feeling that they were appreciated as 'A valuable contributing member of society' (Clare et al, 2008, pp.19) for the contributions they made through dementia-related activism (Bartlett, 2014a;Clare et al, 2008). Others highlighted that their dignity was preserved when they were 'Feeling appreciated and acknowledged…' for their contributions within their family network (Tranvåg et al, 2015, pp.582).…”
Section: Theme: Being Treated As Lesser Compared To a Full And Valuedmentioning
confidence: 99%
“…People described feeling that they had been "socially demoted" (Beard andFox, 2008, pp.1517) and were now treated like second-class citizens (Bartlett, 2014a). They felt that they no longer had equal power within their relationships (Harris and Sterrin, 1999), were looked down upon (Mok et al, 2007), and lacked dignity and respect from others (Barlett, 2014a; Clare et al, 2008). This change in social status was reported by two studies within a theme of loss (Langdon et al, 2007;Mok et al, 2007) Taken from the theme: Dialectical tension between agency and objectification (MacQuarrie, 2005, pp.432) In a study of activism, Bartlett (2014a) found that perceived social relegation motivated some to take action to improve the position of people with dementia in society.…”
Section: Sub-theme: Disempowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Haslam and colleagues (2009) articulate the psychological and physical health benefits of these memberships as being a form of 'social cure'. Research demonstrating the benefits of social identification extends from reducing depression (Cruwys, South, Greenaway, & Haslam, 2014), protecting against stress (Gallagher, Meaney, & Muldoon, 2014;Häusser, Kattenstroth, van Dick, & Mojzisch, 2012), improving health behaviours , and dealing with dementia, brain injury and strokes (Clare, Rowlands, & Quin, 2008;Haslam et al, 2008;Walsh, Muldoon, Gallagher, & Fortune, 2015). Notably, social identification has also been shown to aid recovery from a wide range of traumatic experiences including the Sivas Massacre in Turkey (Yildiz & Verkuyten, 2011), political violence in Northern Ireland (Muldoon & Downes, 2007) and homelessness (Thomas, Gray, McGinty, & Ebringer, 2011).…”
mentioning
confidence: 99%